Determinants and Social Support of Contraception Use - Mega Octamelia (Green Publisher Indonesia, 2022)
The population growth rate in Indonesia is still high. Indonesia ranks 4th in the list of countries with the highest population after China, India, and the United States. This population growth rate is caused by several factors, namely birth factors, death factors and migration factors. Efforts to deal with the high rate of population growth is the use of contraception. The purpose of this study is to analyze the determinants (age, education, number of children, occupation) and social support (husband support, cadre support) with the use of contraception in the Mambirdan Timur Village, Tarakan City, North Kalimantan. This research is a quantitative analytic study with a cross sectional approach. The sample technique used simple random sampling technique and obtained as many as 42 people. Bivariate test in determining the relationship between determinants and social support with the use of contraception using chi square. The results showed that age (p = 0.963), education (p = 0.408), number of children (p = 0.024), occupation (p = 0.856), husband's support (p = 0.000) and cadre support (p = 0.002). The conclusion of this study was that there was a relationship between the number of children and the use of contraception and there was a relationship between husband's support and cadre's support with the use of contraception.